INTEGRASI ILMU AGAMA DAN SAINS DALAM PEMBELAJARAN DI SEKOLAH ISLAM TERPADU: STUDI PERSEPSI SISWA DAN PANDANGAN GURU - Asdianur Hadi; Muh. Irfan Ali; Helmawati Helmawati; Iyad Suryadi (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
The integration of religious knowledge and science is an important issue in contemporary Islamic education due to the persistent separation between religious subjects and general sciences in learning practices. This study aims to describe students’ perceptions and teachers’ views on the integration of religious knowledge and science in learning at an Integrated Islamic School. This research employed a simple descriptive quantitative-qualitative approach. Data were collected through a closed-ended Google Form questionnaire for students and written Google Form interviews with a science teacher, an Islamic education teacher, and a homeroom teacher. The questionnaire data were analyzed using mean scores and tendency categories, while the written interview data were analyzed thematically. The findings indicate that students’ perceptions of the integration of religious knowledge and science were in the very good category. Students perceived learning not merely as the acquisition of scientific knowledge, but also as a process connected to Islamic values, the greatness of Allah, and everyday life. Teachers’ views show that integration is understood as an effort to connect learning materials with Qur’anic verses, hadith, Islamic values, awareness of Allah’s creation, and students’ character formation. The main challenges in implementing integration include limited time, references, teachers’ understanding, and the continued separation between religious and general subjects. This study confirms that integrating religious knowledge and science has the potential to strengthen meaningful learning, spiritual awareness, and students’ character. ABSTRAK Integrasi ilmu agama dan sains merupakan isu penting dalam pendidikan Islam kontemporer karena masih kuatnya pemisahan antara pelajaran agama dan pelajaran umum dalam praktik pembelajaran. Penelitian ini bertujuan untuk mendeskripsikan persepsi siswa dan pandangan guru terhadap integrasi ilmu agama dan sains dalam pembelajaran di Sekolah Islam Terpadu. Penelitian ini menggunakan pendekatan deskriptif kuantitatif-kualitatif sederhana. Data dikumpulkan melalui angket tertutup berbasis Google Form kepada siswa dan wawancara tertulis berbasis Google Form kepada guru IPA, guru PAI, dan wali kelas. Data angket dianalisis menggunakan skor rata-rata dan kategori kecenderungan, sedangkan data wawancara tertulis dianalisis secara tematik. Hasil penelitian menunjukkan bahwa persepsi siswa terhadap integrasi ilmu agama dan sains berada pada kategori sangat baik. Siswa merasakan bahwa pembelajaran tidak hanya mengajarkan ilmu pengetahuan, tetapi juga menghubungkannya dengan nilai Islam, kebesaran Allah, dan kehidupan sehari-hari. Pandangan guru menunjukkan bahwa integrasi dipahami sebagai upaya menghubungkan materi pelajaran dengan ayat Al-Qur’an, hadis, nilai keislaman, kesadaran terhadap ciptaan Allah, dan pembentukan karakter siswa. Kendala utama dalam pelaksanaan integrasi meliputi keterbatasan waktu, referensi, pemahaman guru, dan masih adanya pemisahan antara pelajaran agama dan pelajaran umum. Penelitian ini menegaskan bahwa integrasi ilmu agama dan sains berpotensi memperkuat makna pembelajaran, kesadaran spiritual, dan karakter siswa.